MARKET EVALUATION MODEL: TOOL FORBUSINESS DECISIONS - Porlles Loarte, José (2006)
In the present work the concepts of potential market and global market are analyzed as the basis for strategic decisions of market with long term perspectives, when the implantation of a business in certain geographic area is evaluated. On this conceptual frame, the methodological tool is proposed to evaluate a commercial decision, for which it is taken as reference the case from the brewing industry in Peru, considering that this industry faces in the region entrepreneurial reorderings within a growth strategy.